Morbid Obesity with Complications (Journal of Dhaka National Medical College & Hospital, 2014)
Over weight technically refers to an excess of body weight. where as obesity refer to an excess of fat. The Body Mass Index (BMI) is the accepted standered measure of overweight and obesity BMI provides a guideline for weight in relation to height and is equal to the body weight divided by the height in meters squared. Adults with a BMI between 25 and 30 are considered  overweight, those with a BMI of 30 are considerd to be obse. In adults, a BMI threshed of 40 kg/m2, distinguishes individuals with severe obesity and the high risks for co-morbidities. This category is sometimes termed as "Class 111 obesity" or "Super obesity" or "Morbid obesity". The term Morbid obesity is sometimes used to identify individuals with obesity related co-morbidities. The likelihood of persistence of childhood obesity into adulthood is related to age, parental obesity, and severity of obesity. In longitudinal studies, approximately those 50% of obese 6 years old children, and 80% of obese 10 to 14 years old children. who had an obese parent. Girls are more prone than boys to develop persistent obesity during adolescence. This is related to changes in body composition that occur at puberty, when body fat decreases in boys and increases in girls.J. Dhaka National Med. Coll. Hos. 2014; 20 (02): 63-64